(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to analyze the influence of Lifestyle, Brand Image, Service Quality and product quality on the decision to purchase kopi kenangan in Purwokerto. The research method was quantitatively through a questionnaire with a 5-point Likert Scale assessment for each statement item. Respondents in this study were consumers of coffee who had bought at least 1 time. The sample obtained was a study of 125 respondents. The data was analyzed using SPSS Version 25. The results of the analysis showed that lifestyle and product quality had a significant positive effect on purchase decisions, while brand image and service quality did not have a significant positive effect on purchase decisions. The implications of the research results show that coffee has good product quality and describes the lifestyle of the people in Purwokerto.